2019
DOI: 10.1021/acscatal.8b04345
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic π-Bonding of Imidazolyl Substituent in a Formally 16-Electron Cp*Ru(κ2-P,N)+ Catalyst Allows Dramatic Rate Increases in (E)-Selective Monoisomerization of Alkenes

Abstract: Alkene isomerization can be an atom-economical approach to generating a wide range of alkene intermediates for synthesis, but fully equilibrated mixtures of disubstituted internal alkenes typically contain significant amounts of the positional as well as geometric (E and Z) isomers. Most classical catalyst systems for alkene isomerization struggle to kinetically control either positional or E/Z isomerism. We report coordinatively unsaturated, formally 16-electron Cp*Ru catalyst 5, which facilitates simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…This was partially successful, in that crystals of BArF salt 64 suitable for X‐ray diffraction were obtained, even if the recrystallized bulk material was not uniform and may have contained another non‐identified species, likely a coordination/solvation isomer ( Scheme 9 ,b ; Figure 6). Related complexes with substituted cyclopentadienyl units have been structurally characterized by Grotjahn and Vidovic and coworkers, and it was shown that depending on the steric requirements of the cyclopentadienyl and the phosphine donor groups, either two, one or no acetonitriles bind to the ruthenium center [65,112] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was partially successful, in that crystals of BArF salt 64 suitable for X‐ray diffraction were obtained, even if the recrystallized bulk material was not uniform and may have contained another non‐identified species, likely a coordination/solvation isomer ( Scheme 9 ,b ; Figure 6). Related complexes with substituted cyclopentadienyl units have been structurally characterized by Grotjahn and Vidovic and coworkers, and it was shown that depending on the steric requirements of the cyclopentadienyl and the phosphine donor groups, either two, one or no acetonitriles bind to the ruthenium center [65,112] …”
Section: Resultsmentioning
confidence: 99%
“…Related complexes with substituted cyclopentadienyl units have been structurally characterized by Grotjahn and Vidovic and coworkers, and it was shown that depending on the steric requirements of the cyclopentadienyl and the phosphine donor groups, either two, one or no acetonitriles bind to the ruthenium center. [65,112]…”
Section: Chiral Triazinyldiphosphinyl Pnp Pincer Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Steric factors have proven essential in controlling the selectivity in olefin isomerization. Grotjahn and coworkers observe distinct selectivity based on the cyclopentadienyl substitution pattern in Ru catalysts, 7,59 for example, and Jiao, Liu, and coworkers saw large variations in selectivity as a function of steric parameter in pincer-ligated Co catalysts. 60 These observations suggest that the two catalyst states in a responsive system should be sterically distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Steric factors have proven essential in controlling the selectivity in olefin isomerization. Grotjahn and coworkers observe distinct selectivity based on the cyclopentadienyl substitution pattern in Ru catalysts, 7,59 for example, and Jiao, Liu, and coworkers saw large variations in selectivity as a function of steric parameter in pincer-ligated Co catalysts. 60 These observations suggest that the two catalyst states in a responsive system should be sterically distinct.…”
Section: Discussionmentioning
confidence: 99%